Study on the side venting characteristics of coal mine gas explosions - Yulong Duan; Zishuang Zhang; Li Deng; Xianqi Duan; Rui Lang; Fenglin Cao (Case Studies in Thermal Engineering)
To effectively solve the current coal mine gas explosion problem, an explosion experimental platform has been built independently, and a side venting channel is equipped with the side wall of the explosion pipe, aiming to study how the height of the side venting channel and the location of the side vent affect the characteristics of the gas explosion in the coal mine. The study results show that the flame propagation distance increases with the height of the side venting channel. In contrast, the maximum flame propagation velocity decreases with increased venting channel height. Compared with the case without side wall venting, the attenuation rate of the maximum flame propagation velocity reaches 39.85 %. Furthermore, in the downstream stage, the explosion overpressure of the three different side vent locations decreases with the venting channel height. Reducing the distance between the detonation vent and the ignition source can reduce the explosion pressure. When the side venting channel height is 40mm, the pressure rise rate of double vent positions 1 and 2 decreases by 59.86 %. The results of this study provide a theoretical basis for the prevention and control of coal mine gas explosion sources and neighboring areas.